PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH DI BMT UGT NUSANTARA CABANG JOMBANG - Huluk, Husnul; Santoso, Rohmad Prio (Jurnal Riset Manajemen dan Akuntansi, 2023)
This research was conducted to see how influential promotions carried out by institutions/companies were in introducing their product and how much influence service quality had in shaping customer loyalty to products and institutions/companies. This research is a quantitative research through a positivist philosophy approach. As a test material, 30 people with member status at the Jombang Branch of the BMT UGT Nusantara were used using a non-probability sampling technique. The expected data in this study were collected through questions in the form of a questionnaire. The results of the data obtained from the 30 respondents were tested using SPSS version 25 which included multiple linear regression tests, then the hypothesis was tested using the t test, then the f test and the R2 test. The results concluded that promotion and service quality implemented by BMT UGT Nusantara Jombang Branch had an influence of 36.5% on the formation of customer loyalty, based on the results of the R2 test. Based on the results of the t-count test, promotions partially have an effect of 2.395 > 2.0484 as a t-table value. Likewise, service quality also has a partial effect with a tcount of 2.228 > 2.0484 ttable. Then simultaneously, both of them have an influence on customer loyalty with an fcount value of 9.326 > 3.34 from the ftable value with a significance of 0.001 <0.05.